CAD/CAM systems justification, implementation, productivity measurement - Coticchia, Mark E. (Mechanical engineering (Marcel Dekker, Inc.), 1993)
This edition has been thoroughly updated and expanded to reflect the state-of-the-practice of CAD/CAM/CAE systems.;Maintaining and enhancing the style of presentation of the first edition, CAD/CAM/CAE Systems (second edition) aims to provide a broad, solid understanding of each critical issue involved with the implementation and evaluation of systems; gives industry tested cost justification models to assess the feasibility of purchasing or leasing a system; supplies step-by-step explanations of every aspect of implementation, from initial facility planning to long-term maintenance; shows how to prepare personnel for a new system, including job skills, training stages, organization, and adminstration; illustrates a complete system audit, including five important approaches to determining overall success, six areas that can be judged separately, the dangers of benchmarking, and a two-year follow-up study; and more.;Furnishing the most up-to-date methods, CAD/CAM/CAE Systems, Second edition offers new features such as: a study of the proliferation of personal computers and their role in organizations; a discussion of the benefits and drawbacks of value added remarketers as an alternative to purchasing from conventional CAD/CAM companies; an examination of the cost-effectiveness of third party service organizations; and more. CAD/CAM/CAE Systems is intended as a guide for software, hardware, mechanical, manufacturing, industrial, and design engineers; draftspersons; managers; purchasing agents, acquisition personnel, and company officers responsible for deciding on CAD/CAM/CAE system implementation or augmentation; and graduate-level and continuing-education students in these disciplines.